The Impact of Education and Social Demographic Factors on Female Labor Force Participation in Indonesia - Lusiyanti; Padang Wicaksono (MUWAZAH : jurnal kajian gender, 2020)
The World Economics Forum released the Global Gender Gap Index report 2020 which shows that women's participation in the economy is still lower than women's participation in education. This study aims to analyze how education and socio-demographic factors influence women's work participation in Indonesia. The data source used in this study is the 2019 National Labor Force Survey (Sakernas) from the BPS-Statistics Indonesia. The research method used is descriptive analysis and inferential analysis with the probit model. The probit model is a statistical model to see the probability of a dependent variable that is categorical (1 if a female is working and 0 if she doesn't work). The results of this study indicate that the level of education and social-demographic factors have a significant effect on the probability of female to work. The probability of female to work is higher with increasing their education. Meanwhile, the social- demographic factor that increases the probability of women to work are their status as the head of the family and age. The socio-demographic factors that tend to reduce the probability of female to work are marriage status, existence of children under five in household, and living in urban areas.